Strategies For Teaching Reading At The Second Grade Of Mts Muhammadiyah Blimbing In 2015/2016 Academic Year - HARTOMO, NOPA; , Mauly Halwat Hikmat, S.Pd., M. Hum.,Ph.D; , Nur Hidayat, S. Pd (2016)
The questioning in reading class is important because it encourages the student to learn more and practice. Questioning is one parameter and helps the teacher to know how far the students get their reading comprehension. In general this study aims to mention and describe of strategies used by teacher in teaching reading comprehension and to describe types teacher's questions of strategies in teaching reading comprehension of MTs Muhammadiyah Blimbing in 2015/2016 academic year. The type of this research is descriptive qualitative research. The writer collects the data by observing the teaching learning process, conducting interview with teacher and students, and taking documentation during teaching-learning process.The technique for analyzing data is data reduction, data display, and conclusion. The results of this research show that: 1. Teacher's strategies used by teacher in teaching reading comprehension in MTs Muhammadiyah Blimbing in 2015/2016 academic year in this study are: memorizing, question answer relationship, game and discussion. 2. Types teacher's questions of strategies in teaching reading comprehension of MTs Muhammadiyah Blimbing in 2015/2016 academic year asked by the teacher show that in all the three lessons, yes/no questions, referential question and closed & display questions were rarely or even never asked. However, the referential questions themselves will not make students produce longer responses unless the teachers are able to encourage their students to elaborate further and rather than just accepting those brief and syntactically less complex responses.